Cytomegalovirus early and late membrane antigens detected by antibodies in human convalescent sera. - Middeldorp, J M (1985)
Using indirect immunofluorescence and a panel of human convalescent-phase sera, we identified cytomegalovirus (CMV) early and late membrane antigens (CMV-EMA and CMV-LMA, respectively) as separate entities on the surfaces of viable CMV-infected fibroblasts starting at 6 to 12 and 36 to 48 h postinoculation, respectively. For expression of CMV-EMA and CMV-LMA, infectious virus and active protein synthesis were required, whereas the expression of CMV-LMA, in addition, required viral DNA synthesis. Our data suggest that CMV-EMA and CMV-LMA form an individual set of CMV antigens that are different from intracellular CMV antigens and possibly (partly) different from the viral envelope.